SUMBANGAN MOHD. SAID SULAIMAN SEBAGAI PENYUNTING TRAVELOG KISAH PELAYARAN MUHAMMAD IBRAHIM MUNSYI - Hamdan, Rahimah (JURNAL MELAYU SEDUNIA, 2020)
This paper discusses the contribution of Mohd. Said Sulaiman as the early Malay editor who connected the traditional and modern era in the travelogue, Kisah Pelayaran Muhammad Ibrahim Munshi. Mohd Said’s prowess as a Johore Malay figure was not only due to the fact that he was an important individual in the government (being the Sultan’s private secretary) but that he was also a very prolific scholar in the field of Malay literature. He produced several Malay literary works, either in prose or poetry, culminating in the completion of the major task of introducing these works to Sultan Ibrahim of Johore, who finally decreed that Ibrahim Munsyi’s travelogue to be printed and edited in a scholarly manner. Thus, began Mohd Said Sulaiman’s journey as the connector between the traditional era (the manuscript) and the modern era (the printing press) until this work could continue in the form of the text as it is today. As a result, Kisah Pelayaran Muhammad Ibrahim Munsyi was successfully published for the first time in 1919. It is apparent that the contribution of the late Mohd Said also paved the way and provided useful input to the history of Johore and the West Coast of Peninsular Malaysia, which had only relied on the reports of British officials, which were slanted more towards ’white supremacy’. Indirectly, the complete works edited by him can promote the study of various disciplines such as social studies and humanities. Finally, research has shown that Mohd Said Sulaiman is one of the greatest literary figures of Johore because of his far-sighted vision, which gained prominence for the Johore Government on the world stage.